Peran dan tantangan wanita: Era revolusi industri 4.0 dan era society 5.0 - Khasanah, Sintia Nurul (Maliki Interdisciplinary Journal, 2024)
The development of technology in the era of the Fourth Industrial Revolution and Society 5.0 has brought significant impacts on the roles and challenges faced by women. Women have a strategic role as educators, workers, and agents of development in society. They need to enhance their skills in information technology and communication to actively participate in daily life and seize existing opportunities. Despite having great potential, women face challenges such as low participation rates in the workforce and limited female graduates in the industrial field. The Fourth Industrial Revolution and Society 5.0 should be opportunities for women to develop their potential and contribute to the progress of civilization. Efforts are needed to change societal perspectives and overcome practices that hinder women’s progress in achieving gender equality and sustainable development.